Being Posthuman Through Biopolitics in Neal Shusterman's Unwind - Lingga Gumilang; Pratiwi Retnaningdyah (Tell : Teaching of English Language and Literature Journal, 2022)
This paper explores the concept of posthumanism through biopolitics. Although the goal of biopolitics is to manage the social population, this ideology promotes the oppression of the subject. Shusterman reveals this concept through his novel, Unwind. This novel not only presents the oppression of the subject of the regulation but also shows that the regulation creates a new norm in society that lead them to become posthuman. In other words, the regulation tries to modify humanity into a new form. Using the Foucauldian theory, this paper argues that biopolitics could be a factor for humans to transform into a new type of humanity—posthuman. The result finds that biopolitics in the novel leads to the two types of posthuman; the first is that posthuman emerging human with technology to enhance human being; the second is about reconsideration position of humans. The idea of posthuman might make people resist oppression and embrace other existence as equal beings as humans. This would create better humanity for human beings.